2001
DOI: 10.1007/s001670100226
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency energy induced heating of bovine articular cartilage: comparison between temperature-controlled, monopolar, and bipolar systems

Abstract: This in vitro investigation characterized temperature changes associated with radiofrequency (RF) energy induced heating of bovine articular cartilage using temperature-controlled, monopolar (Vulcan RF system and Vulcan, TAC-S Electrothermal Probe) and bipolar (VAPR II RF system and VAPR TC RF electrode) electrosurgical equipment. The RF generators were used at the same setting (set temperature 70 degrees C; 30 W). The cartilage tissue sample was placed in a saline bath maintained at room temperature. Temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
20
0
2
Order By: Relevance
“…[18][19][20][21]23,24,[46][47][48] In this study, we had concerns about thermal injury to the neighboring articular cartilage. A thorough radiologic and histologic evaluation did not show any evidence of damage to the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21]23,24,[46][47][48] In this study, we had concerns about thermal injury to the neighboring articular cartilage. A thorough radiologic and histologic evaluation did not show any evidence of damage to the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently being used extensively in the arthroscopic setting to debride cartilaginous or meniscal lesions even though its safety has been questioned. [15][16][17][18][19][20][21][22][23][24] As limb length discrepancy and angular deviations constitute a relatively frequent situation in pediatric orthopaedics, we hypothesized that radiofrequency may be an efficient and minimally invasive way to achieve complete or partial growth arrest to treat these conditions. This study was conducted to verify this hypothesis through a single application of radiofrequency energy to the proximal tibial growth plate in white New Zealand rabbits.…”
mentioning
confidence: 99%
“…The temperature at the surface and below the surface of the articular cartilage adjacent to the RFE probe reached 66–74°C upon stimulation with a monopolar device [23, 24]. Such temperatures induce heat shock necrosis in osteoblasts [25].…”
Section: Discussionmentioning
confidence: 99%
“…Shellock et al 19 reported that this new bRFE maintained the temperature at the RFE electrode-tissue interface relatively close to the RFE preset temperature and may be useful for thermal-assisted chondroplasty. Shellock et al 19 reported that this new bRFE maintained the temperature at the RFE electrode-tissue interface relatively close to the RFE preset temperature and may be useful for thermal-assisted chondroplasty.…”
Section: Rfe Application Principlesmentioning
confidence: 96%